Behavior of Providing Additional Recovery Food to Increase Weight of Malnourished Toddlers Aged 24-59 Months at Magetan District Health Center - Suharto, Agung; Harviandani, Berliana Septy (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The percentage of under-five malnutrition problems in Indonesia was 17.8%, with 3.8% and 14% of under-five cases being malnutrition. The Magetan Health Service reports that as of 2021, there were 332 cases of undernourished toddlers; however, the Panekan Health Center reported 116 cases of undernourished toddlers in 2020 based on weight/body length data. The undernourished toddlers was defined as those who were between the ages of 24 and 59 months. This kind of study employs secondary data sources, an analytical approach, a quasi-experimental design, and a non-equivalent control group design. This study included 73 toddlers as subjects: 31 toddlers who did not receive any nutrition, 42 toddlers who did receive nutrition, and malnourished toddlers aged 24-59 months. Data collection uses data collection sheets. The Independent and Paired t-tests are the analysis methods employed. The average difference in body weight between the two groups was found to be 0.594 with a range of 0.0324 kilograms – 1.156 kilograms. The study's results were obtained using the Paired t-test with a p-value = 0.000 with a significance level of 0.05 and the independent t-test with a p-value = 0.038 with a significance level of 0.05. The study concludes that supplementary feeding has an impact on the weight of undernourished toddlers at the Panekan Health Center who are between the ages of 24 and 59 months. It is hoped that by continuing to supplement food, the recovery program may decrease the number of undernourished children under five.